A Low-Profile Reflector-Enhanced Drop-Shaped Printed Antenna for Wide-Band Wireless Communications - Giovanni Cappelletti; Diego Caratelli; Renato Cicchetti; Claudio Gennarelli; Massimiliano Simeoni; Orlandino Testa (International Journal of Antennas and Propagation)
An improved low-profile printed antipodal drop-shaped dipole antenna for wide-band wireless applications is presented. The proposed radiating structure is integrated with a planar metal reflector useful to enhance antenna gain up to 5.5 dBi and the front-to-back ratio up to 21 dB. The geometry of reflector, feeding line, and dipole arms is optimized in order to achieve a broad operating bandwidth useful to meet the requirements of modern wireless communication protocols. Furthermore, the particular shape of the metal reflector and the adoption of a thin low-permittivity dielectric substrate result in a low distortion of the radiated field and a limited back radiation which makes the antenna suitable for UWB applications as well. These features, together with the low profile and the limited occupation area, make the antenna well adapted to mobile terminals as well as radio base stations. A locally conformal FDTD numerical procedure has been adopted to design and analyse the radiating structure, while a SEM technique has been employed to highlight the field perturbation caused by the antenna reflector as well as to extract the characteristics underlying the transient behaviour of the antenna. The experimental measurements performed on an antenna prototype are found to be in good agreement with the numerical computations.